C-Phycocyanin Suppresses the In Vitro Proliferation and Migration of Non-Small-Cell Lung Cancer Cells through Reduction of RIPK1/NF-κB Activity - Shuai Hao; Shuang Li; Jing Wang; Lei Zhao; Yan Yan; Tingting Wu; Jiawen Zhang; Chengtao Wang (Marine Drugs, 2019)
Phycocyanin, derived from Spirulina platensis, is a type of natural antineoplastic marine protein. It is known that phycocyanin exerts anticancer effects on non-small-cell lung cancer (NSCLC) cells, but its underlying mechanism has not been elucidated. Herein, the antitumor function and regulatory mechanism of phycocyanin were investigated in three NSCLC cell lines for the first time: H358, H1650, and LTEP-a2. Cell phenotype experiments suggested that phycocyanin could suppress the survival rate, proliferation, colony formation, and migration abilities, as well as induce apoptosis of NSCLC cells. Subsequently, transcriptome analysis revealed that receptor-interacting serine/threonine-protein kinase 1 (RIPK1) was significantly down-regulated by phycocyanin in the LTEP-a2 cell, which was further validated by qRT-PCR and Western blot analysis in two other cell lines. Interestingly, similar to phycocyanin-treated assays, siRNA knockdown of RIPK1 expression also resulted in growth and migration inhibition of NSCLC cells. Moreover, the activity of NF-κB signaling was also suppressed after silencing RIPK1 expression, indicating that phycocyanin exerted anti-proliferative and anti-migratory function through down-regulating RIPK1/NF-κB activity in NSCLC cells. This study proposes a mechanism of action for phycocyanin involving both NSCLC apoptosis and down regulation of NSCLC genes.